Improving post-thawed sperm quality in Boer goats: The role of thawing duration and vitamin E - Tran, Thi Thanh Khuong; Ngo, Quoc Khanh; Nguyen, Lam Khanh Duy (Vietnam Journal of Biotechnology, 2026)
Cryopreservation is a widely used technique for the long-term storage of animal genetic material, but freezing and thawing can cause significant damage to sperm cells. This study aimed to optimize thawing protocols and post-thaw conditions to improve the quality of cryopreserved Boer goat sperm. Two thawing durations (30 and 60 seconds) and four concentrations of vitamin E (0 mM, 1 mM, 2 mM, and 3 mM) were tested to determine their effects on sperm motility, viability, and membrane integrity. Semen samples from two Boer bucks were cryopreserved and later thawed at 37°C for either 30 or 60 seconds. Post-thaw, sperm were incubated in TCG medium with vitamin E supplementation. The results showed that sperm thawed for 30 seconds with 2 mM vitamin E achieved the highest motility (63.66%), viability (72.16%), and membrane integrity (46.68%), significantly outperforming other treatments (p < 0.05). Although thawing time had no significant effect on membrane integrity, the addition of 2 mM vitamin E consistently improved overall sperm quality. These findings suggest that a 30-second thawing time combined with 2 mM vitamin E supplementation is the optimal protocol for maintaining the quality of cryopreserved Boer goat sperm.